The essentials of Android application development - Clifton, Ian G., 1983-; Safari eBooks ([Place of publication not identified] : Addison-Wesley, 2016)
"In this video training, Ian starts with the installation of Android Studio, configuring an emulator, preparing a device for development, and creating a simple 'hello world' app. He then systematically covers each of the essential parts of Android application development, starting with views, activities, and fragments. Using an AsyncTask to perform background operations comes next, and then services, BroadcastReceivers, and system notifications are explained. The video continues with saving data via SharedPreferences and the file system and enhancing the UI with themes and animations and finishes with tips for becoming more efficient with Android Studio and how to submit an app to the Play Store. After watching this video series, developers will be able to create Android applications from scratch and dive into advanced Android topics."--Resource description page.
Title from title screen (viewed January 7, 2016).
Presenter, Ian G. Clifton.
Keywords: Android (Electronic resource); Mobile apps; Application software; Electronic books